2011
DOI: 10.1007/s12088-011-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacterial Community in the Ginseng Soil Using Denaturing Gradient Gel Electrophoresis (DGGE)

Abstract: The objective of this work was to determine the shifts in the PCR-DGGE profiles of bacterial communities associated with the rhizosphere soil of ginseng at varying age levels. Differences in the dominance of intense DNA bands in the DGGE profile was observed over the age of the plants indicating the fluctuation in the microbial community structure. The bacterial orders of actinomycetales of Actinobacteria and Spingomonadales and Rhizobiales of a-Proteobacteria were predominant in the ginseng soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
(4 reference statements)
7
9
1
1
Order By: Relevance
“…The BIOLOG profiles, which could not separately represent the activity of bacterial or fungal communities, were the total values of microbial communities. The main finding in this study was that the cultivation of P. ginseng , especially cultivation ages, exerted the most profound influence on the genetic and functional diversity in P. ginseng rhizosphere soil, which is consistent with the results of previous studies [21] , [30] , [31] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The BIOLOG profiles, which could not separately represent the activity of bacterial or fungal communities, were the total values of microbial communities. The main finding in this study was that the cultivation of P. ginseng , especially cultivation ages, exerted the most profound influence on the genetic and functional diversity in P. ginseng rhizosphere soil, which is consistent with the results of previous studies [21] , [30] , [31] .…”
Section: Discussionsupporting
confidence: 92%
“…Soil samples were collected from five replicate plots randomly distributed over the fields. The entire root system along with rhizosphere soil was collected by digging at a depth of 20 cm from five healthy plants, and sampling was performed as described previously [21] , [22] . Soil samples of different cultivation ages and modes of P. ginseng were used directly for DNA extraction using the UltraClean Soil DNA Isolation Kit (Mo Bio Laboratories Inc., Bohemia, NY, USA) according to the manufacturer's instructions [23] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al [23] reported a significant impact from 8 years of reclamation and cultivation on the structure and taxonomic composition, and TN and CEC were noted to be potentially important factors for soil microbial composition and function. Furthermore, other studies indicated that the long-term effect of reclamation was essential for improving soil TN content and soil fertility, which are the major factors responsible for shifts in soil community structures [57]. In general, the shifts in bacterial community structure under different environments may not only be ascribed to some significant changes in the soil properties, but also to soil fertility and TN change caused by reclamation measure amendment.…”
Section: Impact Of Soil Properties On the Relative Abundances Of Bactmentioning
confidence: 99%
“…Additionally, relatively few studies have evaluated the relationship between rusty root and changes in the microbial community of the rhizosphere of P. ginseng. Most investigations on rusty root have only considered one microbial species, while not all predominant microbial groups can be detected due to the limitations of traditional molecular methods, such as polymorphic DNA amplification [31] and denaturing gradient gel electrophoresis [32], and the results obtained using these methods have been inconsistent. erefore, whether rusty root is caused by multiple pathogenic microorganisms, rather than just one, remains unknown.…”
Section: Introductionmentioning
confidence: 99%